2019
DOI: 10.7150/jca.30041
|View full text |Cite
|
Sign up to set email alerts
|

miR-1307-3p Stimulates Breast Cancer Development and Progression by Targeting SMYD4

Abstract: Recent studies show that dysregulated miRNAs play an important role in breast cancer initiation and progression. Here, we identified upregulated expression of miR-1307-3p in breast cancer tissues and that increased level of miR-1307-3p was closely correlated with lower survival rate in breast cancer patients. Consistent with clinical data, our in vitro data show that expression level of miR-1307-3p was significantly increased in breast cancer cell lines compared to human mammary epithelial cell line MCF10A. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 14 publications
4
44
0
Order By: Relevance
“…For instance, Tang et al showed that miR-1307-3p acts as a tumour suppressor inhibiting the expression of the BCL2 protein in colorectal carcinogenesis cell lines [37]. However, Han et al show that miR-1307-3p in MCF10A stimulated cell proliferation [38].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tang et al showed that miR-1307-3p acts as a tumour suppressor inhibiting the expression of the BCL2 protein in colorectal carcinogenesis cell lines [37]. However, Han et al show that miR-1307-3p in MCF10A stimulated cell proliferation [38].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1307-5p and miR-1307-3p were obtained by modifying the 5′ telomere and 3′ telomere of the precursors of miR-1307. Previous studies have shown that miR-1307 may promote the proliferation of prostate cancer cells by targeting FOXO3A [27], that downregulation of SMYD4 by miR-1307-3p can influence the occurrence and development of breast cancer cells [28], and that miR-1307-3p affected the growth and metastasis of hepatocellular carcinoma by inhibiting the DAB2 interacting protein [29]. However, the role of miR-1307-5p in lung adenocarcinoma and its molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested miRNAs could either suppress or promote tumor initiation and progression [12][13][14]. MiR-34a, an miRNA well-studied for its association with tumorigenesis, is commonly downregulated in multiple cancers, including osteosarcoma [15], colorectal carcinoma [16], prostate cancer, [17] and liver cancer [18].…”
Section: Introductionmentioning
confidence: 99%